2009
DOI: 10.1016/j.neuroimage.2009.03.048
|View full text |Cite
|
Sign up to set email alerts
|

Regional gray matter variation in male-to-female transsexualism

Abstract: Gender identity-one's sense of being a man or a woman-is a fundamental perception experienced by all individuals that extends beyond biological sex. Yet, what contributes to our sense of gender remains uncertain. Since individuals who identify as transsexual report strong feelings of being the opposite sex and a belief that their sexual characteristics do not reflect their true gender, they constitute an invaluable model to understand the biological underpinnings of gender identity. We analyzed MRI data of 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
133
4
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 154 publications
(154 citation statements)
references
References 42 publications
9
133
4
8
Order By: Relevance
“…This setup ensured a very reliable sample of 'early-onset' individuals with GD. Savic and Arver (2011) examined GM in 'non-homosexual' MF using VBM and volumetric delineation and did not observe any signs of feminization, and Luders et al (2009b) detected only a localized feminization of the right putamen in primarily 'non-homosexual' MF. Luders et al (2012) also examined cortical thickness in MF, observing some deviations from the natal sex in several regions, although the lack of a female control sample did not facilitate determining whether these deviations reflect signs of feminization.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This setup ensured a very reliable sample of 'early-onset' individuals with GD. Savic and Arver (2011) examined GM in 'non-homosexual' MF using VBM and volumetric delineation and did not observe any signs of feminization, and Luders et al (2009b) detected only a localized feminization of the right putamen in primarily 'non-homosexual' MF. Luders et al (2012) also examined cortical thickness in MF, observing some deviations from the natal sex in several regions, although the lack of a female control sample did not facilitate determining whether these deviations reflect signs of feminization.…”
Section: Discussionmentioning
confidence: 98%
“…MRI studies examining white matter tracts using diffusion tensor imaging have shown deviations from the natal sex in white matter microstructure in both female-to-males (FM) and male-to-females (MF) (Rametti et al, 2011a,b). A few neuroimaging studies have investigated gray matter (GM) in individuals with GD, observing both regional volumetric properties in line with the natal sex and others in line with the gender identity of the GD groups (Luders et al, 2009b(Luders et al, , 2012Savic and Arver, 2011;Zubiaurre-Elorza et al, 2012;Simon et al, 2013). A recent study by Zubiaurre-Elorza et al (2012) was the first to examine GM in FM (ZubiaurreElorza et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In auditory processing untreated MtFs showed differences compared with women in earlier and compared with men in higher processing stages. In line with previous structural studies (Luders et al., 2009; Rametti et al., 2011) our data underline the exceptional position of MtFs. Hormonal treatment seems to shift MtFs more toward their aspired gender.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, MtFs presented a unique pattern of rs‐FC, which cannot be easily assigned to either of the two sexes. This confirms previous findings suggesting an exceptional position of MtFs distinct from men and women (Luders et al., 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation